PAI Learning Design Using the Addie Model in Welcome Material, O My Prophet, Beloved of Allah SWT at Wyata Dharma Middle School, Bandung - Mulyawan Safwandy Nugraha; Muhammad Kafnun Kafi; Ujang Dedih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This research is intended to describe the use of the ADDIE model in teaching Islamic Religious Education (PAI) with a focus on material regarding